Reflex modulation after long term passive repeated plyometric training - Liu, C.; Chang, Y. J.; Chen, C. -S.; Shiang, T. Y. (ISB Congress, 2005)
The purpose of this study was to investigate the excitability of the reflex arc and the presynaptic inhibition (PSI) could be modulated by the Passive Repeated Plyometric training (PRP training).